The Relationship Between Mental State and Functional Status in Elderly Residents of Kahrizak - Hadi Kazemi; Sima Ghasemi; Farshad Sharifi; Hossein Fakhrzadeh; Maryam Ghaderpanahi; Mojde Mirarefin; Mahshid Foroughan; parvaneh Mohammadkhani (Sālmand, 2010)
Objectives: The current study was performed to investigate the relationship between mental impairment and each component of activity of daily living (ADL) in elderly residents of the Kahrizak Charity Foundation.